A Compact High-Precision Cascade PID-Control Laser Driver for Airborne Coherent LiDAR Applications - Ming, Zixuan; Li, Xianzhuo; Wang, Yanyi; Qu, Yuanzhe; Lu, Zhiyong; Jia, Honghui; Yuan, Haoming; Zhang, Qianwu; Zhang, Junjie; Song, Yingxiong (Sensors (Basel, Switzerland), 2025)
This paper solves the challenge of precise dual-frequency laser control in Airborne Coherent Doppler LiDAR systems by implementing an innovative laser driver architecture, which integrates compact hardware design with cascade Proportional-Integral-Derivative (PID) control and a frequency–temperature compensation mechanism. The experimental results demonstrate eminent performance with long-term temperature fluctuation below 0.007 °C, temperature stabilizing time under 4 s and long-term power fluctuation of the linear constant current source being <1%. The system enables wide-range temperature–frequency adjustment for individual lasers and dynamically adjusts the dual-laser beat frequencies between −1 GHz and +2 GHz, achieving the frequency difference fluctuation within 3 MHz. These achievements greatly enhance LiDAR performance and create possibilities for broader applications in dynamic environmental sensing, atmospheric monitoring, deep-space exploration, and autonomous systems.